A Stable Crystalline Triarylphosphine Oxide Radical Anion - Schaub, Tobias; Zolnhofer, Eva; Halter, Dominik; Shubina, Tatyana; Hampel, Frank; Meyer, Karsten; Kivala, Milan (Angewandte Chemie International Edition, 2016)
Triarylphosphine oxides (Ar3P=O) are being intensely studied as electron-accepting (n-type) materials. Despite the widespread application of these compounds as electron conductors, experimental data regarding the structural and electronic properties of their negatively charged states remain scarce owing to their propensity for follow-up chemistry. Herein, a carefully designed triarylphosphine oxide scaffold is disclosed that comprises sterically demanding spirofluorenyl moieties to shield the central phosphoryl (P=O) moiety. This compound undergoes chemical one-electron reduction to afford an exceptionally stable radical anion, which was isolated and characterized by X-ray crystallography for the very first time. The experimental data, corroborated by computational studies, shall allow for the construction of phosphine oxide materials with enhanced stability.
EAM Import::2019-03-13

Binary supramolecular networks of bridged triphenylamines with different substituents and identical scaffolds - Steiner, Christian; Yang, Zechao; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Ammon, Maximilian Michael; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Chemical Communications, 2018)
Based on scanning tunneling microscopy experiments combined with density functional theory, we report the formation and the electronic structure of porous binary supramolecular networks on Au(111). The two triphenylamine derivatives with identical scaffolds intermix due to a maximization of the overall number of H-bonds instead of an optimization of the H-bond strength in the bonding motif. The HOMO-LUMO gap is defined by both molecules, which is typical for electron donor-acceptor networks.

Configurationally Stable Chiral Dithia-Bridged Hetero[4]helicene Radical Cation: Electronic Structure and Absolute Configuration - Gliemann, Bettina; Petrovic, Ana G.; Zolnhofer, Eva; Dral, Pavlo O.; Hampel, Frank; Breitenbruch, Georg; Schulze, Philipp; Raghavan, Vijay; Meyer, Karsten; Polavarapu, Prasad L.; Berova, Nina; Kivala, Milan (Chemistry - An Asian Journal, 2017)
A stable chiral hetero[4]helicene radical cation was synthesized and characterized by UV/Vis absorption and EPR spectroscopy, as well as X-ray crystallography. For the first time, a combination of chiroptical methods involving ECD, ORD, and VCD, supported by quantum mechanical predictions, enabled the elucidation of the absolute configuration of such open-shell helical species.
EAM Import::2019-03-13

Cyano-Functionalized Triarylamines on Au(111): Competing Intermolecular versus Molecule/Substrate Interactions - Gottardi, Stefano; Muller, Kathrin; Moreno-Lopez, Juan Carlos; Yildirim, Handan; Meinhardt, Ute; Kivala, Milan; Kara, Abdelkader; Stohr, Meike (Advanced Materials Interfaces, 2014)
The self-assembly of cyano-substituted triarylamine derivatives on Au(111) is studied with scanning tunneling microscopy and density functional theory calculations. Two different phases, each stabilized by at least two different cyano bonding motifs are observed. In the first phase, each molecule is involved in dipolar coupling and hydrogen bonding, while in the second phase, dipolar coupling, hydrogen bonding and metal-ligand interactions are present. Interestingly, the metal–ligand bond is already observed for deposition of the molecules with the sample kept at room temperature leaving the herringbone reconstruction unaffected. It is proposed that for establishing this bond, the Au atoms are slightly displaced out of the surface to bind to the cyano ligands. Despite the intact herringbone reconstruction, the Au substrate is found to considerably interact with the cyano ligands affecting the conformation and adsorption geometry, as well as leading to correlation effects on the molecular orientation.
EAM Import::2019-03-13

Cyano-Functionalized Triarylamines on Coinage Metal Surfaces: Interplay of Intermolecular and Molecule-Substrate Interactions - Muller, Kathrin; Moreno-Lopez, Juan Carlos; Gottardi, Stefano; Meinhardt, Ute; Yildirim, Handan; Kara, Abdelkader; Kivala, Milan; Stohr, Meike (Chemistry - A European Journal, 2016)
The self-assembly of cyano-functionalized triarylamine derivatives on Cu(111), Ag(111) and Au(111) was studied by means of scanning tunnelling microscopy, low-energy electron diffraction, X-ray photoelectron spectroscopy and density functional theory calculations. Different bonding motifs, such as antiparallel dipolar coupling, hydrogen bonding and metal coordination, were observed. Whereas on Ag(111) only one hexagonally close-packed pattern stabilized by hydrogen bonding is observed, on Au(111) two different partially porous phases are present at submonolayer coverage, stabilized by dipolar coupling, hydrogen bonding and metal coordination. In contrast to the self-assembly on Ag(111) and Au(111), for which large islands are formed, on Cu(111), only small patches of hexagonally close-packed networks stabilized by metal coordination and areas of disordered molecules are found. The significant variety in the molecular self-assembly of the cyano-functionalized triarylamine derivatives on these coinage metal surfaces is explained by differences in molecular mobility and the subtle interplay between intermolecular and molecule-substrate interactions.
EAM Import::2019-03-13

Dithiafulvenyl-Extended N-Heterotriangulenes and Their Interaction with C60: Cooperative Fluorescence - Gliemann, Bettina; Strauß, Volker; Hitzenberger, Jakob; Dral, Pavlo O.; Hampel, Frank; Gisselbrecht, Jean-Paul; Drewello, Thomas; Thiel, Walter; Guldi, Dirk Michael; Kivala, Milan (Chemistry - A European Journal, 2017)
We describe the synthesis as well as the electronic and photophysical characterization of novel N-heterotriangulene derivatives decorated with methoxycarbonyl- and methyl-sulfanyl-substituted dithiafulvenyl moieties. The association of these electron-rich compounds with fullerene C60 as electron acceptor was investigated by means of photophysical, voltammetric, and mass spectrometric methods and rationalized by DFT calculations. Importantly, light-induced interactions between the dithiafulvene-substituted N-heterotriangulene bearing methoxycarbonyl substituents with C60 leads to cooperative fluorescence. Quantitative Job plot analyses by means of fluorescence spectroscopy and voltammetry confirm a 1:1 association with binding constants in the order of 104 m-1. Supportive results for the supramolecular assembly of both N-heterotriangulenes with C60 were obtained by ESI mass spectrometric investigations in the gas phase.
EAM Import::2019-03-13

Doped polycyclic aromatic hydrocarbons as building blocks for nanoelectronics: a theoretical study - Dral, Pavlo; Kivala, Milan; Clark, Timothy (Journal of Organic Chemistry, 2013)
Density functional theory (DFT) and semiempirical UHF natural orbital configuration interaction (UNO-CI) calculations are used to investigate the effect of heteroatom substitution at the central position of a model polycyclic aromatic hydrocarbon. The effects of the substitution on structure, strain, electronic and spectral properties, and aromaticity of the compounds are discussed.

Hierarchical on-surface synthesis and electronic structure of carbonyl-functionalized one- and two-dimensional covalent nanoarchitectures - Steiner, Christian; Gebhardt, Julian; Ammon, Maximilian Michael; Yang, Zechao; Heidenreich, Alexander; Hammer, Natalie; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nature Communications, 2017)
The fabrication of nanostructures in a bottom-up approach from specific molecular precursors offers the opportunity to create tailored materials for applications in nanoelectronics. However, the formation of defect-free two-dimensional (2D) covalent networks remains a challenge, which makes it difficult to unveil their electronic structure. Here we report on the hierarchical on-surface synthesis of nearly defect-free 2D covalent architectures with carbonyl-functionalized pores on Au(111), which is investigated by low-temperature scanning tunnelling microscopy in combination with density functional theory calculations. The carbonyl-bridged triphenylamine precursors form six-membered macrocycles and one-dimensional (1D) chains as intermediates in an Ullmann-type coupling reaction that are subsequently interlinked to 2D networks. The electronic band gap is narrowed when going from the monomer to 1D and 2D surface-confined π-conjugated organic polymers comprising the same building block. The significant drop of the electronic gap from the monomer to the polymer confirms an efficient conjugation along the triphenylamine units within the nanostructures.

Long-range energy transport in single supramolecular nanofibres at room temperature - Haedler, Andreas T.; Kreger, Klaus; Issac, Abey; Wittmann, Bernd; Kivala, Milan; Hammer, Natalie; Koehler, Juergen; Schmidt, Hans-Werner; Hildner, Richard (Nature, 2015)
Efficient transport of excitation energy over long distances is a key process in light-harvesting systems, as well as in molecular electronics. However, in synthetic disordered organic materials, the exciton diffusion length is typically only around 10 nanometres (refs 4, 5), or about 50 nanometres in exceptional cases, a distance that is largely determined by the probability laws of incoherent exciton hopping. Only for highly ordered organic systems has the transport of excitation energy over macroscopic distances been reported–for example, for triplet excitons in anthracene single crystals at room temperature, as well as along single polydiacetylene chains embedded in their monomer crystalline matrix at cryogenic temperatures (at 10 kelvin, or -263 degrees Celsius). For supramolecular nanostructures, uniaxial long-range transport has not been demonstrated at room temperature. Here we show that individual self-assembled nanofibres with molecular-scale diameter efficiently transport singlet excitons at ambient conditions over more than four micrometres, a distance that is limited only by the fibre length. Our data suggest that this remarkable long-range transport is predominantly coherent. Such coherent long-range transport is achieved by one-dimensional self-assembly of supramolecular building blocks, based on carbonyl-bridged triarylamines, into well defined H-type aggregates (in which individual monomers are aligned cofacially) with substantial electronic interactions. These findings may facilitate the development of organic nanophotonic devices and quantum information technology.
EAM Import::2019-03-12

N-Heterotriangulene chromophores with 4-pyridyl anchors for dye-sensitized solar cells - Meinhardt, Ute; Lodermeyer, Fabian; Schaub, Tobias; Kunzmann, Andreas; Dral, Pavlo O.; Sale, Anna Chiara; Hampel, Frank; Guldi, Dirk Michael; Costa, Ruben Dario; Kivala, Milan (RSC Advances, 2016)
A series of dimethylmethylene-bridged N-heterotriangulenes decorated with one, two, and three electron-withdrawing 4-pyridyls were synthesized. Their photophysical and electrochemical characteristics were examined and their successful application in n-type TiO2- and ZnO-based dye-sensitized solar cells demonstrated the ability of the 4-pyridyl moiety to act as an anchor.
EAM Import::2019-03-12

N-Heterotriangulenes: Fascinating Relatives of Triphenylamine - Hammer, Natalie; Schaub, Tobias; Meinhardt, Ute; Kivala, Milan (Chemical Record, 2015)
Carbonyl- and dimethylmethylene-bridged triphenylamines called N-heterotriangulenes are not only aesthetically pleasing extgreekp-conjugated scaffolds interesting on their own but also provide numerous possibilities for further synthetic modifications to serve as versatile precursors for the construction of functional organic molecules. In this Personal Account we give a historical synopsis depicting the long way from the initial synthesis of N-heterotriangulenes back in the 1970s to their derivatization followed by recent applications in organic electronics. As a part of our ongoing research on heteroatom-doped extgreekp-conjugated scaffolds we provide an overview of our synthetic efforts involving the N-heterotriangulene scaffolds and discuss the optoelectronic, redox, and self-assembly properties of the resulting molecular entities.
EAM Import::2019-03-12

p-Doping of graphene in hybrid materials with 3,10-diazapicenium dications - Roth, Alexandra Marina; Schaub, Tobias; Meinhardt, Ute; Thiel, Dominik; Storch, Jan; Cirkva, Vladimir; Jakubik, Pavel; Guldi, Dirk Michael; Kivala, Milan (Chemical Science, 2017)
N,N′-Didodecyl-substituted 3,10-diazapicenium salts featuring bromide and hexafluorophosphate counterions have been designed as novel dopants to realize individualized graphene sheets in a series of cutting edge experiments and to intrinsically stabilize them via p-doping. Importantly, electrochemical studies revealed two consecutive irreversible one-electron reductions of the N,N′-didodecyl-substituted 3,10-diazapicenium salts to yield the corresponding radical cation and neutral quinoidal species. Formation of both species was accompanied by characteristic changes in the absorption spectra. The 3,10-diazapicenium bromide was found to be a potent dopant to produce hybrid materials with exfoliated graphene. Microscopy based on AFM and TEM imaging and spectroscopy based on Raman probing corroborated that, upon drying, the hybrid material consists of few layer (5–8 layers) turbostratic graphene sheets that are p-doped. Our findings identify the newly synthesized N,N′-dialkylated 3,10-diazapicenium salts as highly promising candidates for the fabrication of functional graphene materials with tailored properties.
EAM Import::2019-03-08

Self-Assembly and Stability of Hydrogen-Bonded Networks of Bridged Triphenylamines on Au(111) and Cu(111) - Steiner, Christian; Gliemann, Bettina; Meinhardt, Ute; Gurrath, Martin; Meyer, Bernd; Kivala, Milan; Maier, Sabine (Journal of Physical Chemistry C, 2015)
The adsorption, chemical nature, and self-assembly of diaminotriazinyl- and carboxyl-substituted triphenylamines with dimethylmethylene bridges were studied on Au(111) and Cu(111) at submonolayer coverage by low-temperature scanning tunneling microscopy and density functional theory. On Au(111), both molecules form extended porous honeycomb networks. The geometry of the networks agrees well with density functional theory optimized hydrogen-bonded gas phase structures. Therefore, the self-assemblies on Au(111) are strongly directed by intermolecular hydrogen bond interactions. In contrast, on Cu(111) both molecules aggregate in dense islands owing to the stronger moleculesurface interaction. While the carboxyl substituents partially deprotonate at room temperature on Cu(111), the diaminotriazinyl-substituted triphenylamines adsorb mainly intact. The diaminotriazinyl groups deprotonate gradually at increased adsorption temperatures.

Stability of Odd- Versus Even-Electron Gas-Phase (Quasi)Molecular Ions Derived from Pyridine-Substituted N-Heterotriangulenes - Hitzenberger, Jakob; Dral, Pavlo O.; Meinhardt, Ute; Clark, Timothy; Thiel, Walter; Kivala, Milan; Drewello, Thomas (ChemPlusChem, 2017)
Electrospray ionisation of N-heterotriangulenes (i.e., dimethyl-methylene-bridged triphenylamines) with up to three pyridyl groups at their periphery, produces the true radical cation ([M](+center dot)) and the protonated molecule ([M+H](+)) simultaneously. These ions are studied as model systems to illustrate the stability alternation of odd-versus even-electron ions in energy-dependent collision-induced dissociation (CID) experiments. All ions show the same fragmentation pattern, the consecutive loss of three methyl radicals ((CH3)-C-center dot) from the dimethylmethylene bridges of the central triangulene core. [M](+center dot) ions dissociate at much lower collision energies than their [M+H](+) counterparts. The radical cation forms a singlet fragment with an extended aromatic system that is energetically favoured. Ab initio and density functional theory calculations support this interpretation and allow the assignment of the electronic structure of the fragment ions. Consecutive collision-induced dissociations provide a better match with theory when studied with an ion trap, rather than a linear quadrupole. This is attributed to the resonant nature of the excitation of intermediate ions.
Keywords: ab initio calculations; collision-induced dissociation; density functional calculations; electrospray ionisation; mass spectrometry; N-heterotriangulenes

Synthesis and Photophysical Properties of Multichromophoric Carbonyl-Bridged Triarylamines - Haedler, Andreas T.; Beyer, Sebastian R.; Hammer, Natalie; Hildner, Richard; Kivala, Milan; Koehler, Juergen; Schmidt, Hans-Werner (Chemistry - A European Journal, 2014)
The synthesis and photophysical properties of two novel multichromophoric compounds is presented. Their molecular design comprises a carbonyl-bridged triarylamine core and either naphthalimides or 4-(5-hexyl-2,2'-bithiophene)naphthalimides as second chromophore in the periphery. The lateral chromophores are attached to the core via an amide linkage and a short alkyl spacer. The synthetic approach demonstrates a straightforward functionalization strategy for carbonyl-bridged triarylamines. Steady-state and time-resolved spectroscopic investigations of these compounds, in combination with three reference compounds, provide clear evidence for energy transfer in both multichromophoric compounds. The direction of the energy transfer depends on the lateral chromophore used. Furthermore, the compound bearing the lateral 4-(bithiophene)naphthaimides is capable of forming fluorescent gels at very low concentrations in the sub-millimolar regime whilst retaining its energy transfer properties.
EAM Import::2019-03-12

Synthesis and Properties of Arylvinylidene-Bridged Triphenylamines - Hammer, Natalie; Shubina, Tatyana; Gisselbrecht, Jean-Paul; Hampel, Frank; Kivala, Milan (Journal of Organic Chemistry, 2015)
A series of arylvinylidene-bridged triphenylamines were efficiently synthesized through the thionation/Barton-Kellogg olefination sequence from their corresponding carbonyl precursors. The electrochemical investigations identified these highly distorted scaffolds as fairly strong electron donors capable of several reversible oxidation steps with the first oxidation occurring at a potential comparable to that of ferrocene for the n-hexyl-substituted diphenylvinylidene-bridged compound.
EAM Import::2019-03-12

Tandem mass spectrometry of π-expanded triphenylamine and N-heterotriangulene scaffolds: Radical cation versus silver(I) adduct - Kinzelmann, Marina; Fröhlich, Nina; Vogel, Alexander; Kivala, Milan; Drewello, Thomas (Journal of Mass Spectrometry, 2024)
Triphenylamine (TPA) and N-heterotriangulene (N-HTA) scaffolds with up to three oligophenyl extensions are investigated by electrospray ionization (tandem) mass spectrometry (ESI-[MS/]MS). Due to their low oxidation potentials, all molecules readily form radical cations in the electrospray process. The energy-resolved collision-induced dissociation behaviour of the molecular ions is contrasted to that of the silver(I) adducts. Complexation with Ag(I) leads to the expected [1:1] and [2:1] complexes (MAg+ and M2Ag+); however, even [1:2] complexes (MAg22+) can be detected for molecules with two and three large π-expansions to allow stabilization of two charges. The TPA scaffolds decompose only at high collision energies through the loss of peripheral tert-butyl groups. A general mechanism for this is proposed commencing with a methyl loss and followed by the release of isobutene and butyl radical moieties. The N-HTA-based scaffolds are considerably less stable and molecular ions fragment at low collision energies. This is caused by the facile loss of methyl radicals from the dimethylmethylene-bridged triangulene core. In contrast, complexation with Ag+ leads to a dramatic stabilization. Most interestingly, dissociation eventually proceeds via the loss of neutral AgCH3, which is indicative of strong bidentate, tweezer-like bonding of Ag+ to the molecules.
CRIS-Team Scopus Importer:2024-08-23
Keywords: CH; energy-resolved collision-induced dissociation; radical cation; silver(I) adduct; π-extended triphenylamine and N-heterotriangulene

Two-dimensional delocalized states in organometallic bis-acetylide networks on Ag(111) - Yang, Zechao; Gebhardt, Julian; Schaub, Tobias; Sander, Tim; Schönamsgruber, Jörg; Soni, Himadriben; Görling, Andreas; Kivala, Milan; Maier, Sabine (Nanoscale, 2018)